Customer Satisfaction dan Behavioral Intention di McDonald’s - Indra Perdana Wibisono (Journal of Tourism and Creativity, 2019)
Abstract Increasing public economic development has in turn made increasing public activities. Thus, in the highly competitive service industries such as fast food restaurants, it is very essential to satisfied customer. This may be achieved through the high quality of the service, food, and price the service provided by producer. The objective of this research was: (a) the positive effect of service quality on customer satisfaction, (b) the positive effect of food quality on customer satisfaction, (c) the positive effect of price/value on customer satisfaction, (d) the positive effect of customer satisfaction on behavioural intention. The design of this research applies a survey on McDonald’s restaurant as the unit of analysis by interviewing in the customers to test the hypothesis. The data consist of five variables including service quality, food quality, and price/value attribute as independent variables, customer satisfaction as intervening variable and behavioural intention as dependent variable. A number of 177 customers were selected as the respondents this research. Data analysis used in this research consists of Structural Equation Method by LISREL software. The results of this research concluded that variables of service quality, food quality, and price/value had positive effects on customer satisfaction, and variable of customer satisfaction had positive effect on behavioural intention. Keyword: service quality, food quality, price/value, customer satisfaction dan behavioral intention